Dowling-Degos disease: a case report and clinicopathological correlation of a rare genodermatosis - Lai, Shau Kong; Mohd Nasir, Noor 'ain; Wan Ahmad Kammal, Wan Syahira Ellani; Abu, Nasiha; Tak, Nor Akmar; Tan, Yi Jun (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Dowling-Degos disease (DDD), also termed reticulate pigmented anomaly of the flexure, is a rare genodermatosis characterized by reticulate pigment macules, typically appearing after puberty. We describe a male patient, age 55, who has hyperpigmented papules and macules over the nape of his neck and flexures. The condition was initially diagnosed as lichen planus pigmentosus and has persisted for the past three years. Family history revealed similar skin conditions in maternal siblings and their mother. Skin biopsy demonstrated epidermal changes consistent with DDD, including filiform down-growth epidermis, thinning of suprapapillary plates, and basal layer hyperpigmentation. We discussed the broad differential diagnoses that mimic this condition. Correlating clinical, pathological, and genetic features is essential for its diagnosis. As this genodermatosis is typically resistant to treatment, specific therapies such as laser treatments have shown promise in managing DDD. This emphasizes the importance of correct diagnosis.